Effect of different feeding regimes in amur common carp fingerlings: compensatory growth, physio-metabolic responses, and expression of IGF-1 gene - Chowdhury Arka; Ghosh Tapas Kumar; Khatua Sanjib; Hore Sayani; Kumari Palak; Kajal Kumari; Jana Prasanta (Aquatic Living Resources)
The experiment was intended to evaluate the competent restricted feeding strategy for amur common carp fingerlings reared under actual pond condition. Fingerlings (2.28 ± 0.27 g) were subjected to five different restricted feeding regimes; viz. TC (daily feeding), T1/1 (1-day feeding/ 1-day starvation), T2/1 (2-days feeding/ 1-day starvation), T2/2 (2-days feeding/ 2-days starvation), and T1/2 (1-day feeding/ 2-days starvation). The results indicated significantly similar (P > 0.05) growth pattern in T2/1, when compared to TC. But in other feed-deprived groups the fish growth was much poor. In T2/1, the feeding strategy had no significant adverse effect on SGR; rather it supported improved nutrient utilization indices. T2/1 asserted superior digestive capacity in the starved group, with elevated (P < 0.05) protease and amylase activity. Reduced (P < 0.05) hepatic lactate dehydrogenase and malate dehydrogenase activity in T2/1 group suggests reduced stress, which might strengthen compensatory growth. Feed deprivation increased (P < 0.05) both alanine aminotransferase and aspartate aminotransferase activity in blood. In the current study, elevated (P < 0.05) level of hepatic superoxide dismutase, catalase, glutathione peroxidase activity and Insulin like growth factor 1 and reduced (P < 0.05) blood glucose level, parallel to the degree of starvation was also evidenced. The present study suggests that 2-day feeding followed by 1-day feed restriction (T2/1) as the best feeding strategy for pond culture of amur common carp with the highest net return without compromising the growth, yield and antioxidative status.